Individual optimization of the repulsion biomechanism When jumping up - Bilenko A. G.; Losin, B. E.; Ivanova, G. P. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to find the optimal repulsion technique depending on the individual characteristics of the athlete.